2018
DOI: 10.1002/macp.201800398
|View full text |Cite
|
Sign up to set email alerts
|

Alternating Placement of d‐ and l‐Alanine Moieties in the Polymer Side‐Chains

Abstract: Synthesis of a sequence‐controlled polymer via reversible addition‐fragmentation chain transfer polymerization is reported herein, using an N‐substituted maleimide monomer bearing tert‐butyl carbamate (Boc)‐protected l‐alanine (M1) and Boc‐d‐alanine appended styrenic monomer (M2). The monomer sequence distribution along the polymer chain is thoroughly studied by 1H and 13C NMR spectroscopy and matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry, confirming the alternating placement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Similarly for P4 , the quaternary aromatic carbon (a) and methylene carbon (c) signals were appeared at 135.1 and 35.0 ppm, respectively (Figure S9B). Although it was reported that the copolymerization of an equimolar mixture of styrene and maleimide gave the alternating copolymer with the poly­(styrene- alt -maleimide) backbone, our abovementioned studies also signified the alternating placement of monomers along the copolymer chains …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly for P4 , the quaternary aromatic carbon (a) and methylene carbon (c) signals were appeared at 135.1 and 35.0 ppm, respectively (Figure S9B). Although it was reported that the copolymerization of an equimolar mixture of styrene and maleimide gave the alternating copolymer with the poly­(styrene- alt -maleimide) backbone, our abovementioned studies also signified the alternating placement of monomers along the copolymer chains …”
Section: Resultsmentioning
confidence: 95%
“…Although it was reported that the copolymerization of an equimolar mixture of styrene and maleimide gave the alternating copolymer with the poly(styrene-alt-maleimide) backbone, 33 our abovementioned studies also signified the alternating placement of monomers along the copolymer chains. 34 The number average molecular weight (M n,GPC ) and dispersity (D̵ ) values of the copolymers were determined from the GPC study. Note that the free COOH groups of copolymers were converted to tert-butyl ester groups before using these in GPC analysis.…”
Section: H Nmr Study and Esi-ms Spectroscopy (Figures S6−s8)mentioning
confidence: 99%
“…The detailed characterization of the synthesized copolymers through 1 H NMR, 13 C NMR and size exclusion chromatography (SEC) can be found in our previous report . Herein, we utilized RAFT polymerization method to have the polymers with well-defined molecular weight, narrow dispersity ( Đ ) and defined chain ends . The polymers were designated according to the following example: when MF = MP and VBP = VBP750 , the copolymer was assigned as P­(MP- alt -VBP750).…”
Section: Resultsmentioning
confidence: 99%
“…1 , the synthetic route depicts the synthesized block copolymer consisting of PEGMA and long-chain fatty acid repeating unit. RAFT polymerization was employed to obtain polymers with controlled molecular weight as well as a defined chain terminal, 37 herein we also have used RAFT polymerization technique to obtain core–shell lipid polymer hybrid nanoparticle for drug delivery application using CDSP as CTA. The homopolymer poly(PEGMA) was synthesized by using CTA and AIBN as a thermal initiator at a feed ratio of PEGMA : CDSP : AIBN = 50 : 1 : 0.25.…”
Section: Resultsmentioning
confidence: 99%